CLINICAL PROFILES OF FROSTBITE IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL: A CASE SERIES - Wahyu Nugroho, Thomas Eduardus Sudrajat; Beta Subakti Nata’atmadja (Jurnal Rekonstruksi dan Estetik, 2019)
Highlights: This study presents three cases of frostbite in adults who participated in a Mount Denali expedition, highlighting the treatment process and outcomes. The importance of long-term follow-up management and prioritizing finger preservation and potential reconstruction in patient care. Abstract: Introduction: Frostbite is a common cold-related injury, especially among mountaineers in high-altitude settings. These injuries can occur both in freezing and above-freezing temperatures. The main goal of this study is to understand the clinical aspects of frostbite cases treated at Dr. Soetomo General Academic Hospital in Surabaya. Case Illustration: We present three cases of frostbite in adults who were part of a Mount Denali expedition, reaching an altitude of 6192 meters. Initial treatment included rewarming and pain relief. They were admitted to our facility 11st days after the injury, with one patient undergoing finger amputation on the 71st day. All received standard antibiotics and three days of hospital care. No initial surgeries were performed; instead, wound checks and rehabilitation were done as outpatients. On the 71st day, one patient had the third and fourth fingers amputated. The study found changes in platelet counts during the acute frostbite phase but no significant changes during the subacute phase following cold exposure. Discussion: The cases showed substantial improvements in wound healing, reduced swelling, increased mobility, and overall better health. Clear demarcation of damaged tissue occurred during observation. While frostbite is rare in tropical areas, it can impact individuals in cold-weather activities like mountain climbing and winter sports. Effective prevention and management are vital for good outcomes. Initially, conservative treatment is suggested, but surgery may be needed when the extent of tissue damage is apparent. Conclusions: Long-term follow-up management is necessary to achieve a good functional outcome. Preservation and if necessary reconstruction of the finger should become a priority in the patient management.